2014
DOI: 10.1016/j.ajhg.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

A Peroxisomal Disorder of Severe Intellectual Disability, Epilepsy, and Cataracts Due to Fatty Acyl-CoA Reductase 1 Deficiency

Abstract: Rhizomelic chondrodysplasia punctata (RCDP) is a group of disorders with overlapping clinical features including rhizomelia, chondrodysplasia punctata, coronal clefts, cervical dysplasia, congenital cataracts, profound postnatal growth retardation, severe intellectual disability, and seizures. Mutations in PEX7, GNPAT, and AGPS, all involved in the plasmalogen-biosynthesis pathway, have been described in individuals with RCDP. Here, we report the identification of mutations in another gene in plasmalogen biosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 42 publications
1
101
0
1
Order By: Relevance
“…A mutation in exon 9a (p.Asp365Gly) of FAR1 , a gene of the plasmalogen–biosynthesis pathway, causes rhizomelic chondrodysplasia punctata (RCDP), a disease that is characterized by severe intellectual disability with cataracts, epilepsy and growth retardation (Buchert et al , 2014). Novel MXE 9b is expressed in the same tissues but at eightfold lower levels suggesting partial functional compensation of the MXE 9a mutation, which might be responsible for the “milder” form of RCDP as compared to pathogenic mutations in other genes of the pathway ( PEX7, GNPAT and AGPS ) (Appendix Fig S32).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mutation in exon 9a (p.Asp365Gly) of FAR1 , a gene of the plasmalogen–biosynthesis pathway, causes rhizomelic chondrodysplasia punctata (RCDP), a disease that is characterized by severe intellectual disability with cataracts, epilepsy and growth retardation (Buchert et al , 2014). Novel MXE 9b is expressed in the same tissues but at eightfold lower levels suggesting partial functional compensation of the MXE 9a mutation, which might be responsible for the “milder” form of RCDP as compared to pathogenic mutations in other genes of the pathway ( PEX7, GNPAT and AGPS ) (Appendix Fig S32).…”
Section: Resultsmentioning
confidence: 99%
“…Novel MXE 9b is expressed in the same tissues but at eightfold lower levels suggesting partial functional compensation of the MXE 9a mutation, which might be responsible for the “milder” form of RCDP as compared to pathogenic mutations in other genes of the pathway ( PEX7, GNPAT and AGPS ) (Appendix Fig S32). A tissue‐specific compensation mechanism had already been proposed but a reasonable explanation could not be given because FAR2 expression shows a different tissue profile and individuals with deficits in peroxisomal β‐oxidation, a potential alternative supply for fatty alcohols, have normal plasmalogen levels (Buchert et al , 2014). Because of the young age of the affected children, it is not known yet whether a mutation in constitutive exon 4 (p.Glu165_Pro169delinsAsp), which could not be compensated in a similar way as the exon 9a mutation, leads to a strong RCDP‐like phenotype (no survival of the first decade of life) or to a milder form such as the one caused by the exon 9a mutation.…”
Section: Resultsmentioning
confidence: 99%
“…We earlier demonstrated that Far1 activity is regulated by modulating its stability in response to the cellular level of plasmalogens (6,7). Very recently, a plasmalogen-deficient disorder with intellectual disability, epilepsy, and cataracts was shown in a FAR1-defective patient, implying the essential function of Far1 in plasmalogen synthesis (8). However, the physiological consequence of the homeostasis of plasmalogen in cells remains poorly understood.…”
mentioning
confidence: 99%
“…The indispensable role of the peroxisomal enzymes GNPAT (Wanders et al, 1992), AGPS (Wanders et al, 1994), and FAR1 (Buchert et al, 2014) in the formation of etherphospholipids has become clear from the identification of patients with genetically determined deficiencies of these three enzymes. In such patients EPL-synthesis is severely deficient as concluded from the markedly reduced plasmalogen levels in erythrocytes from patients (for reviews see Brites et al, 2004;Malheiro et al, 2015).…”
Section: Ros/rns Metabolismmentioning
confidence: 99%
“…The essential role of peroxisomes in each of these metabolic pathways is emphasized by the fact that a variety of genetic diseases in man has been identified, usually with severe clinical signs and symptoms, that are caused by mutations in genes coding for peroxisomal enzymes involved in each of these metabolic pathways. Table 1 lists the single peroxisomal enzyme deficiencies identified so far including two recently identified peroxisomal disorders including fatty acyl-CoA reductase 1 (FAR1) deficiency (Buchert et al, 2014) and Peroxisomal Membrane Protein 70 (PMP70/ABCD3) deficiency (Ferdinandusse et al, 2015).…”
Section: Introductionmentioning
confidence: 99%